Demographic and clinical characteristics of pediatric traumatic cataract transition. - Q. M. Ismayilov (Pediatric Anesthesia and Critical Care Journal, 2024)
Abstract Introduction The purpose of the study is to evaluate the demographic and clinical profile of patients with the diagnosis of pedi- atric traumatic cataract treated at the university clinic, and the results of treatment. Material and Methods The study was conducted with retrospective observation at the ophthalmology clinic of the Azerbaijan Medical University, the data of 24 patients were examined. Infor- mation was collected on patients' age, gender, place of residence (rural, urban), nature of trauma, time elapsed after trauma, visual acuity, causes of visual impairment, tissues damaged by trauma. Cataracts were removed and an intraocular lens was placed in all patients. The results of the treatment were evaluated according to the compli- cations that occurred during and after the operation, vis- ual acuity. Results All of the children's traumatic cataract cases in our obser- vation were associated with one or more comorbidities. The association of crystal only with corneal winter, sclera and anterior chamber damage is 16.7±7.6, respectively; 8.3±5.6; It was found in 12.5±6.7% of patients. The pres- ence of third pathology (sclera, anterior chamber) against the background of joint damage of the cornea and crystal is 8.3±5.6, respectively; It was found in 12.5±6.7% of pa- tients. Against the background of damage to the crystal, cornea and anterior chamber, the association of the fourth pathology (macular, vitreous body) was recorded in 16.7±7.6 and 12.5±6.7% of patients, respectively. Conclusion Summarizing the clinical and demographic characteris- tics of patients treated with pediatric traumatic cataract at the university clinic, the following conclusions can be drawn: the majority of patients are boys (95.8±4.1%) and are in the age range of 5-18 years, the specific weight of rural residents (75%) and urban residents 3 times more compared to; formation of traumatic cataract in children in most cases (50±10.2%) is observed within 3-6 months, the main reason for referral is corneal clouding and a sharp decrease in visual acuity; Damage to several tissues is typical for pediatric traumatic cataract, although all pa- tients have comorbidity, damage to four tissues in several variants (16.7±7.6% cornea + anterior chamber and mac- ula; 12.5±6.7% crystalline, corneal winter +anterior chamber+bone-like body; 8.3±5.6% crystal+sclera+ret- ina; 4.2±4.1% crystal+cornea+retina) is observed; treat- ment of children's traumatic cataract is observed with complications in 20.8±8.3% cases.